TINGKAT PELAYANAN FASILITAS PEJALAN KAKI DI KAWASAN TRANSIT ORIENTED DEVELOPMENT DUKUH ATAS JAKARTA - Agah Muhammad Mulyadi (Himpunan Pengembangan Jalan Indonesia (HPJI), 2020)
Abstract Transit Oriented Development is an urban development approach that adopts mixed spatial planning and maximizes the use of mass transportation. Dukuh Atas area is the first area in the city of Jakarta to be designated as a Transit Oriented Development area. In this area, the modes of public transportation that are already operating are Electric Railroad, Commuter Line, Mass Rapid Transit, Airport Trains, Transjakarta Buses, and Metrotrans Buses. Jakarta Light Rail Transit and Jabodebek Light Rail Transit will also have stations in the Dukuh Atas area. The purpose of this study is to determine the level of service of pedestrian facilities in the Dukuh Atas. The survey was carried out by manually calculating pedestrian flows and pedestrian travel times. Furthermore, the level of service of pedestrian facilities is determined using parameters of pedestrian flows, pedestrian speed, pedestrian density, and pedestrian space. The results of the analysis show that based on v/c ratio, the level of service on Jalan Blora Road, on Jalan Tanjung Karang, and in the Kendal Tunnel is all A. While based on the queuing area, the level of service varies between A to D. Furthermore, based on the clustering effect, the levels of service obtained were A and B. Keywords: Transit Oriented Development; pedestrian; mass transportation; level of service. Abstrak Transit Oriented Development merupakan suatu pendekatan pengembangan kota yang mengadopsi tata ruang campuran dan memaksimalkan penggunaan transportasi masal. Kawasan Dukuh Atas merupakan kawasan pertama di Kota Jakarta yang dicanangkan sebagai kawasan Transit Oriented Development. Di kawasan ini, moda transportasi umum yang sudah beroperasi adalah Electric Railroad atau Kereta Rel Listrik, Commuter Line, Mass Rapid Transit, Kereta Bandara, Bus Transjakarta, dan Bus Metrotrans. Light Rail Transit Jakarta dan Light Rail Transit Jabodebek juga akan memiliki stasiun di wilayah Dukuh Atas ini. Tujuan studi ini adalah menentukan tingkat pelayanan fasilitas pejalan kaki di kawasan Dukuh Atas. Survei dilakukan dengan cara menghitung secara manual arus pejalan kaki dan waktu tempuh pejalan kaki. Selanjutnya, tingkat pelayanan fasilitas pejalan kaki ditentukan dengan menggunakan parameter arus pejalan kaki, kecepatan pejalan kaki, kepadatan pejalan kaki, dan ruang pejalan kaki. Hasil analisis menunjukkan bahwa berdasarkan v/c ratio, tingkat pelayanan di Jalan Blora, di Jalan Tanjung Karang, dan di Terowongan Kendal semuanya adalah A. Sedangkan berdasarkan area antrian, tingkat pelayanan bervariasi antara A hingga D. Selanjutnya berdasarkan efek pengelompokan, diperoleh tingkat pelayanan A dan B. Kata-kata kunci: Transit Oriented Development; pejalan kaki; transportasi masal; tingkat pelayanan.